Youth Empowerment in Efforts to Improve Self Care and Reproductive Health at the Salafiyah Syafiiyah Islamic Boarding School in Situbondo - Neny Yuli Susanti; Miftakhur Rohmah (Universitas STRADA Indonesia, 2024)
Menstrual pain or dysmenorrhea is a condition that bothers most people current woman menstruation regardless of age with the highest percentage in age early teens who have just experienced menarche. Dysminorrhea is also known as a disorder nature symptomatic means is not a disease but only one of the symptoms that appear and can causes discomfort. The process of occurrence painful period or dysmenorrhea that is on phase proliferation going to phase secretion happen enhancement rate prostaglandins in endometrium in a way excessive Which can This causes myometrium to contract, resulting in subsequent ischemia with a decrease in progesterone levels at the end of the luteal phase. This matter causes pain in the uterine muscles before, during and after menstruation . Activity This community service aims to help increase knowledge and adolescent skills daughter through training activities. Activity targets this is the whole teenager daughter Which Already experience menstruation and have history previous menstrual pain at the Salafiyah Syafiiyah Islamic Boarding School in Situbondo, The expected benefits from training activities include increasing knowledge and mothers' skills regarding the prevention and management of menstrual pain in adolescent girls. The method used in this activity is through tutorials or training. Nara The sources for this activity include students and a team of lecturers from the Faculty of Midwifery Study Program Ibrahimy University of Health Sciences. The results of this activity include young women can handle or provide education to teenagers or students another about benefit from technique acupresseur.